Pelatihan Pengolahan Sampah Botol Plastik Menjadi Sofa Minimalis Bagi Ibu Pkk di Pesisir Sungai Rokan - Misdawita Misdawita; Yelly Zamaya; Supriani Sidabalok (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2023)
The problem of plastic bottle waste is still a big challenge for Riau Province, including the Sedinginan, which is one of the villages traversed by the Rokan river. Plastic bottle waste from households along the Rokan river is disposed of in the river, so that the volume of waste in the river is increasing. Reprocessing plastic bottle waste is an effort to avoid environmental pollution by plastic waste. Through creativity, plastic bottle waste can be recycled into a minimalist sofa that has economic value. This Community Service was carried out by means of training on processing plastic bottle waste into minimalist sofas for PKK Sedinginan. The purpose the activity is to provide them with knowledge and skills on how to process plastic bottle waste into minimalist sofas. The implementation method is by conducting counseling and training to PKK mothers. The result of the activity was an increase in the knowledge and skills of PKK women on how to process plastic bottle waste into goods of economic value. Based on the activities that have been carried out, it can be concluded that there must be ongoing training in plastic waste management, not only in the form of plastic bottles but also other plastics produced from household waste so that people have skills in managing waste.